Screening for genotypic and phenotypic variations in CYP450 activity in patients with therapeutic problems in a psychiatric setting, a retrospective study. (April 2017) - Lloret-Linares, Célia; Rollason, Victoria; Lorenzini, Kuntheavy Ing; Samer, Caroline; Daali, Youssef; Gex-Fabry, Marianne; Aubry, Jean-Michel; Desmeules, Jules; Besson, Marie
Graphical abstract: Abstract: Objectives: This retrospective study aimed to assess to what extent an adverse drug reaction (ADR), an abnormal therapeutic drug monitoring (TDM) or a non-response, was attributable to an abnormal cytochrome P450 activity in a psychiatric setting. Method: We collected the results of investigations performed in these situations related to psychotropic drugs between January 2005 and November 2014. Activities of different cytochrome P450 were assessed by genotyping and/or phenotyping. Two experienced clinical pharmacologists assessed independently the possible association between the event and the results of the investigations. Results: One hundred and thirty eight clinical or biological situations had a complete assessment of all major metabolic pathways of the target drug. A majority of clinical or biological situations were observed with antidepressants (n = 93, 67.4%), followed by antipsychotics (n = 28, 20.3%), benzodiazepines and hypnotics (n = 13, 9.4%), and psychostimulants (n = 4, 2.9%). Genotype and/or phenotype determination was mainly performed because of ADRs (n = 68, 49.3%) or non-response (n = 46, 33.3%). Inter-rate reliability of the scoring system between the pharmacologists was excellent (kappa = 0.94). The probability of an association between ADR, TDM or non-response and metabolic status was rated as intermediate to high in 34.7% of all cases, with proportions of 30.4% and 36.7%, for non-response and ADR respectively. Conclusion: When indicated by clinical pharmacologists, ADR, TDM or non-response may be attributable to a variation of the metabolic status with an intermediate to high probability in 34.7% of patients, based on the congruent assessment made by two clinical pharmacologists. Further studies assessing the clinical relevance of prospective explorations and clarifying the appropriate method according to the clinical context are needed.